MENJADI WARGA NEGARA YANG BAIK: ESENSI ILMU KEWARGANEGARAAN: penelitian kualitatif studi kasus - Sartika, Rinny; PA, Reh Bunga; Setiawan, Deny; Lubis, Juliana Dwi Arifin (Jurnal Gentala Pendidikan Dasar, 2024)
This research aims to describe citizenship science as an important field of study for understanding the rights and obligations of individuals as citizens and their role in national and state life. This study emphasizes the importance of explaining the definition of citizenship science, the purpose of studying it, and its relationship with other scientific disciplines. Apart from that, it discusses the human rights that citizens have and their obligations towards the state and society, as well as the importance of balance between the two. The basic values of citizenship, especially Pancasila, are identified as moral guidelines that must be implemented in everyday life as well as a deep understanding of citizenship to create a just, responsible and competitive society on the global stage. The research approach used is a qualitative research study. cases according to the research focus. The data collection technique used in this research is Literature Study. The research results show that a good understanding of citizenship will encourage individuals to play an active role in society, maintain a balance between rights and obligations, and contribute to the development of a better nation.